Tantangan dan Peluang Keadilan Sosial dalam Penegakan Hukum Bisnis - Irfansyah, Irfansyah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of writing this work is to analyze the challenges and opportunities for social justice in business law enforcement. This study conducted a literature review by collecting and analyzing literature from scientific journals, books, and official documents to explore challenges and opportunities in social justice in business law enforcement. Data was collected through systematic searches, interviews with legal experts and practitioners, and direct observation, to obtain an in-depth perspective. Data analysis was carried out qualitatively with a thematic approach, identifying trends and patterns to draw conclusions about the dynamics of social justice in the context of business law. The results of this work, challenges and opportunities in social justice in business law enforcement, reveal that economic inequality, complex regulations, and inequality in law enforcement are the main obstacles that need to be overcome to create a fair business environment. Legal and regulatory reform is needed to ensure that all parties have equal access to justice and economic opportunities. Partnerships between the public and private sectors can be key to driving inclusive and sustainable change. The use of technology, particularly in increasing the transparency and efficiency of legal processes, has great potential to level the playing field for all parties.